2019
DOI: 10.1111/andr.12718
|View full text |Cite
|
Sign up to set email alerts
|

Myo‐inositol in health and disease: its impact on semen parameters and male fertility

Abstract: Background Myo‐inositol (cis‐1,2,3,5‐trans‐4,6‐cyclohexanehexol; MI) is the most prominent of nine inositol stereoisomers. MI, its phosphate derivatives, and associated lipids are widely found in vegetables and animal tissues and are known to participate in numerous biological processes. Objectives To perform a review analysis on MI presence, functions, and impact in male fertility. Materials and Methods A thorough search of listed publications in PubMed on MI and its derivatives was done. Results Published in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 151 publications
(168 reference statements)
0
22
0
Order By: Relevance
“…In recent years, the SLC5A3 cellular transporter was found to be expressed in several tissues. Among others, testis and epididymis displayed (high/medium/low) expression, while Sertoli cells display elevated expression, as the hypertonic conditions increase MI uptake [119,120]. Therefore, here the concentration of MI is 28 times higher compared to the plasma.…”
Section: Role Of Inositols In Male Fertilitymentioning
confidence: 88%
See 1 more Smart Citation
“…In recent years, the SLC5A3 cellular transporter was found to be expressed in several tissues. Among others, testis and epididymis displayed (high/medium/low) expression, while Sertoli cells display elevated expression, as the hypertonic conditions increase MI uptake [119,120]. Therefore, here the concentration of MI is 28 times higher compared to the plasma.…”
Section: Role Of Inositols In Male Fertilitymentioning
confidence: 88%
“…The absorption of free inositol in the intestine is achieved with an active transporter of sodium/myo-inositol transporter (SMIT) family, temperature and pH dependent. SMIT is an active symporter which allows uptake and accumulation, dependently on both concentration of substrates and energy [119,120]. Furthermore, intestinal absorption of a high amount of myo-inositol is considered safe, as highlighted by several studies that proved the absence of side effects even after ingesting large quantities [118].…”
Section: Role Of Inositols In Male Fertilitymentioning
confidence: 99%
“…Between others, inositols are cyclic carbohydrates existing in nine stereoisomeric forms: myo-inositol is the most abundant form in nature. Several studies have shown that myo-inositol has powerful antioxidant properties that improve sperm quality, particularly in patients with oligoasthenozoospermia [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…GPC is produced by epididymal cells and released in the epididymal lumen; spermatozoa increase their GPC levels at maturation (for review see [45]). Myo-inositol is a carbocyclic sugar involved in cell signal transduction, antioxidant defenses, and osmoregulation; as phosphatidylinositol or as mono or polyphosphates works as a second messenger in many intracellular signal transduction pathways [46]. It is associated with an improved mitochondrial morphology [47] and membrane potential [48].…”
Section: Discussionmentioning
confidence: 99%